Methamphetamine presentations to an emergency department: Management and complications. (28th December 2018) - Isoardi, Katherine Z; Ayles, Sarah F; Harris, Keith; Finch, Clare J; Page, Colin B
Abstract: Objective: There is little recent published data characterising methamphetamine intoxication. The present study aims to describe the clinical effects, management, complications and disposition of patients with methamphetamine exposure. Methods: This is a retrospective review of patients presenting with methamphetamine intoxication to an ED in 2016. All presentations were extracted from a relational database and each medical record reviewed. Demographics, clinical features, complications and disposition were extracted. Results: There were 378 presentations of 329 patients (234 men [71%]), median age 31 years (range 16–68 years). The most common clinical effect was acute behavioural disturbance, occurring in 295 (78%) presentations. This was successfully managed with oral sedation alone in 180 (61%) patients, with the remainder receiving parenteral sedation. Other effects included tachycardia in 212 (56%), hypertension in 160 (42%) and hyperthermia in 17 (5%) presentations. No anti‐hypertensives were given. One patient was actively cooled. Complications included 21 (30%) presentations with rhabdomyolysis and 41 (13%) presentations with acute kidney injury. There were two seizures, three intracranial bleeds and one myocardial infarction. The majority (317 [84%]) of patients were managed solely within the ED. The median length of stay was 14 h. There were 41 (11%) mental health admissions. Two deaths occurred: one following an out‐of‐hospital cardiac arrest and the other a subarachnoid haemorrhage. Conclusion: The main toxicity seen with methamphetamines is acute behavioural disturbance, which is managed well with sedation. Complications, apart from rhabdomyolysis and acute kidney injury, are rare. Most patients are managed within the ED and discharged home.